Long-distance pollen and seed dispersal and inbreeding depression in Hymenaea stigonocarpa (Fabaceae: Caesalpinioideae) in the Brazilian savannah - Moraes, Marcela A.; Kubota, Thaisa Y. K.; Rossini, Bruno C.; Marino, Celso L.; Freitas, Miguel L. M.; Moraes, Mario L. T.; da Silva, Alexandre M.; Cambuim, Jose; Sebbenn, Alexandre M. (Wiley, 2018)
Hymenaea stigonocarpa is a neotropical tree that is economically important due to its high-quality wood; however, because it has been exploited extensively, it is currently considered threatened. Microsatellite loci were used to investigate the pollen and seed dispersal, mating patterns, spatial genetic structure (SGS), genetic diversity, and inbreeding depression in H. stigonocarpa adults, juveniles, and open-pollinated seeds, which were sampled from isolated trees in a pasture and trees within a forest fragment in the Brazilian savannah. We found that the species presented a mixed mating system, with population and individual variations in the outcrossing rate (0.53-1.0). The studied populations were not genetically isolated due to pollen and seed flow between the studied populations and between the populations and individuals located outside of the study area. Pollen and seed dispersal occurred over long distances (>8 km); however, the dispersal patterns were isolated by distance, with a high frequency of mating occurring between near-neighbor trees and seeds dispersed near the parent trees. The correlated mating for individual seed trees was higher within than among fruits, indicating that fruits present a high proportion of full-sibs. Genetic diversity and SGS were similar among the populations, but offspring showed evidence of inbreeding, mainly originating from mating among related trees, which suggests inbreeding depression between the seed and adult stages. Selfing resulted in a higher inbreeding depression than mating among relatives, as assessed through survival and height. As the populations are not genetically isolated, both are important targets for in situ conservation to maintain their genetic diversity; for ex situ conservation, seeds can be collected from at least 78 trees in both populations separated by at least 250 m.
Keywords: Ex situ conservation; Microsatellite loci; Mixed mating system; Neotropical tree